2014
DOI: 10.1890/13-0615.1
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting patterns of allochthony among three major groups of crustacean zooplankton in boreal and temperate lakes

Abstract: The importance of terrestrial-derived organic matter for lake zooplankton communities remains debated, partly because little is known about the basic pathways by which allochthonous carbon is transferred to zooplankton, and whether these vary among the major taxonomic and functional groups. We quantified allochthony of three zooplankton groups (Cladocera, Calanoida, and Cyclopoida) across 18 lakes in Quebec, spanning broad gradients of dissolved organic matter (DOM) and lake trophy, using a multi-isotope (delt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
145
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(164 citation statements)
references
References 48 publications
(112 reference statements)
11
145
8
Order By: Relevance
“…Interestingly, our results suggest a lower limit in bacterial biomass allochthony in the order of~70% even in more productive systems where terrestrial DOC becomes more diluted by algal C (Figure 1). These patterns are coherent with previous studies which noted similar high levels of allochthony of bacterial biomass (79% ± 16) across a wide range in lake productivity or color in Québec on the basis of the isotopic composition of bacterial fatty acids (Berggren et al, 2014), as well as in a lake in northern Sweden (480%) (Karlsson et al, 2012) and Selective carbon consumption and allocation F Guillemette et al in two Wisconsin lakes (Kritzberg et al, 2004), although lower estimates have also been reported in the latter (range of 35-70%). Our results are also consistent with a recent hypothesis, suggesting that the rapid transfer and efficient incorporation of compounds exported from soils and leaf litter, or produced via photochemical degradation, may account for a large share of total bacterial production in boreal streams and lakes (up to 80%) (Berggren et al, 2010a, b).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Interestingly, our results suggest a lower limit in bacterial biomass allochthony in the order of~70% even in more productive systems where terrestrial DOC becomes more diluted by algal C (Figure 1). These patterns are coherent with previous studies which noted similar high levels of allochthony of bacterial biomass (79% ± 16) across a wide range in lake productivity or color in Québec on the basis of the isotopic composition of bacterial fatty acids (Berggren et al, 2014), as well as in a lake in northern Sweden (480%) (Karlsson et al, 2012) and Selective carbon consumption and allocation F Guillemette et al in two Wisconsin lakes (Kritzberg et al, 2004), although lower estimates have also been reported in the latter (range of 35-70%). Our results are also consistent with a recent hypothesis, suggesting that the rapid transfer and efficient incorporation of compounds exported from soils and leaf litter, or produced via photochemical degradation, may account for a large share of total bacterial production in boreal streams and lakes (up to 80%) (Berggren et al, 2010a, b).…”
Section: Discussionsupporting
confidence: 92%
“…Here we used previously published values for these parameters, and also a well-established isotopic model (IsoError; Phillips and Gregg, 2001) to account for their variability, but we cannot discard that some methodological biases, isotopic artifacts or secondary C incorporation pathways such as anaplerotic C fixation may have influenced our estimates of allochthony (See Supplementary Note 1 for a discussion of these issues). It should be emphasized that our estimates of bacterial biomass allochthony fall well within the range recently reported in other regions (Kritzberg et al, 2004;Karlsson et al, 2012;Berggren et al, 2014), and that the patterns in BR of terrestrial C also agree with previous reports, that is, that BR in unproductive lakes is dominated by terrestrial C (Karlsson et al, 2007;Karlsson et al, 2008). In addition, it is unlikely that the link that we found between the patterns of allocation of terrestrial versus algal C in the experimental incubations with ambient lake Chl a and phosphorous concentration (both of which being completely unconnected to the actual isotopic or metabolic mass balance), would emerge from chance or methodological bias, providing further evidence that these patterns in bacterial DOC utilization and allocation across lakes that we describe here are real.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Crustacean zooplankton which comprise cladocerans and copepods are one of the most important organisms, because they occupy an intermediate position between microorganisms (microalgae, rotifers, protozoa, and bacteria) and larger organisms (e.g., fish) (Berggren et al, 2014;Sarma et al, 2006). Meanwhile, because crustacean zooplankton often have wide geographical distributions, sensitive to individual stressors, and their morphology are easy to identify (Cairns et al, 1993), factors affecting community structure of crustacean zooplankton have been studied intensively in the last few years.…”
Section: Introductionmentioning
confidence: 99%